The Nyai Endorsement Phenomenon and the Ethos of Simple Living in Pesantren: Navigating Religious Identity in the Age of Digital Consumerism - Maknunah, Lu’luil; Wafa, Ali; Warits, Abd (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
The emergence of influencers from Islamic boarding school nyai circles who are active in endorsement activities is a new phenomenon that is quite interesting to study. Nyai's character, which is usually used as a means of Islamic preaching, is now being used in economic battles. Nyai, as role models for students and society in general, should display attitudes and behaviors that are in accordance with the teachings in Islamic boarding schools. However, in practice, Nyai endorsements actually appear to display a hedonistic lifestyle that is contrary to the value of simplicity. Based on this anxiety, researchers conducted a study on the practice of endorsing nyai on social media, as well as its impact on the concept of simple living taught in Islamic boarding schools. To analyze and answer this question, researchers collaborated on Vincent Mosco's commodification theory and Pierre Bourdieu's capital theory. This research is included in a phenomenological study with a qualitative research type. Data was obtained by conducting interviews and collecting documents. The results of the research show that in endorsement activities there were efforts to commodify the symbolic capital of the nyai as the kiai's wife/daughter. Apart from that, efforts were also found to commodify the Nyai's cultural capital, which included the Nyai's knowledge, her honest personality, and her skills in styling fashion that was trendy but still in accordance with the Shari'a. From these endorsement activities, it was found that there was an impact on the concept of simple living taught in Islamic boarding schools. Nyai's endorsement has been proven to be able to influence the consumption decisions of students who follow her, although not significantly enough